INTEGRASI KERANGKA CASEL DALAM PENGEMBANGAN MATERI SOCIAL EMOTIONAL LEARNING UNTUK PENGUATAN INTERAKSI SOSIAL SISWA MI - Nurkhairina (Staisman Press, 2025)
Education in the 21st century requires the development of student competencies that do not only focus on academic aspects but also emphasize social and emotional development. The Social Emotional Learning (SEL) approach has become one of the learning strategies capable of integrating these three aspects in a balanced manner. One of the widely used frameworks in implementing SEL is the Collaborative for Academic, Social, and Emotional Learning (CASEL). This framework emphasizes the development of five core competencies, namely self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. This article aims to analyze the importance of implementing the CASEL approach in the Primary Islamic Teacher Education Study Program (PGMI), particularly in the development of Social Emotional Learning–based teaching materials. This study employs a qualitative approach using a literature review method by examining various books and national scholarly journals published within the last ten years. The findings indicate that the integration of the CASEL approach in the development of PGMI teaching materials can improve the quality of learning in a more holistic manner, as it does not only emphasize cognitive aspects but also promotes character development, empathy, and social skills among students as prospective teachers. Therefore, the implementation of CASEL in developing teaching materials in the PGMI study program becomes a strategic step in preparing professional and character-oriented Islamic elementary school teachers.